Impaired synthesis of lipoxygenase products in glutathione synthetase deficiency - Mayatepek, Ertan; Hoffmann, Georg F.; Carlsson, Birgit; Larsson, Agne; Becker, Katja (Pediatric research, 1994)
ABSTRACT: Glutathione synthetase deficiency (GSD) is an inborn error of glutathione (GSH) metabolism leading to a generalized intracellular GSH deficiency. Because GSH is required for leukotriene C4 (LTC4) synthesis, we studied synthesis and metabolism of several lipoxygenase products in two patients with GSD by radio-HPLC, UV spectrophotometry, and enzyme immunoassays. In both patients, LTC4 synthesis was significantly decreased in calcium ionophore-stimulated neutrophils (up to 0.4 ng/ 106 cells; controls, 5.0 ± 0.9) and monocytes (up to 3.6 ng/ 106 cells; controls, 30.2 ± 3.3). LTB4 synthesis was about seven times higher in GSD cells compared with controls, whereas synthesis of other 5-, 12-, and 15-lipoxygenase products and prostaglandin E2 was not affected. Neutrophils and monocytes from both patients showed a marked reduction in capacity to form [3H]LTC4 from[3H]LTA4 (9-14% of control values). Urinary LTE4 was finally found to be 50-fold lower in GSD, reflecting a decreased synthesis of cysteinyl LT in vivo. GSD may serve as a unique model for the linkage between LT synthesis and GSH metabolism in vivo.
Gesehen am 29.10.2025